A Room at a time. How women entered party politics - FREEMAN, Jo (Rowman & Littlefield Pub, 1999)
The prominent political women of today stand upon the shoulders of those who spent the last two hundred years building a foundation for women's political participation. Jo Freeman brings to us the rich story of how American women entered into political life and party politics―well before suffrage and often completely separate from it. She shows that women's early political involvement was focused on the Republican party, very different from the situation today. And she builds up to the explosion of women's political activisim of the 1960s and 1970s, connecting past to future by tracing the roots of key political strategies still being debated in the early 21st century. Now for the first time in paperback, A Room at a Time is considered a landmark of original research into women's political history as well as party politics.